What Frequency of Ankle Pump Exercise is Optimal to Improve Lower Limb Hemodynamics? A Systematic Review and Network Meta-analysis - Xin Wang; Rongsong Tang; Heli Zhang; Fan Li; Jing Wang; Baohua Li (Elsevier, 2023)
Summary: Purpose: Ankle pump exercises (APE) have been widely used in clinical practice. However, best practices for APE have not been established. Recognize the most effective frequency of APE for improving lower extremity hemodynamics and establish recommendations in clinical practice. Methods: Therefore, a systematic review and network meta-analysis (NMA) was performed according to PRISMA-NMA. Six English databases (Pubmed, Medline, CINAHL, Embase, the Cochrane library and ProQuest) and four Chinese databases (CNKI, Wanfang, VIP and Sinomed) were searched. Randomized controlled trials (RCTs) and quasi-experimental studies investigating the effects of different frequencies of APE on lower limb hemodynamics published before July 2022 were included. The reference list was also searched. Seven studies (one RCTs and six quasi-experimental studies) were included in the systematic review and five studies (one RCTs and four quasi-experimental studies) were included in the NMA. The risk of bias was assessed using the Cochrane and Joanna Briggs Institute tools. The NMA was performed using the R software (version 4.2.1) and OpenBUGS (version 3.2.3). Results: The results of the NMA showed that a frequency of every 3-4 s the most effective in improving lower extremity hemodynamics (P =.85), followed by every 1-2 s (P = .81), every 5-6 s (P=.32) and less than every 10 s (P =.02). Subgroup analysis failed to find a difference between healthy participants and those with unilateral total hip arthroplasty or fracture (MD = −0.23, 95% CI-5.92 to 4.61). Conclusions: Consequencely, for adult patients, with or without lower extremity disease, a frequency of every 3-4 s can be recommended as the optimal frequency of APE in clinical care practice. Registered number on PROSPERO: CRD42022349365. https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=349365.